Impact of a Documentation Intervention on Health-Assessment Metrics on an Inpatient Gynecologic Oncology Service [24A]. (May 2018) - Marquiette, Jaclyn; Moss, Haley; Truong, Tracy; Havrilesky, Laura
Abstract : INTRODUCTION: Severity of illness (SOI) and risk of mortality (ROM) scores are determined from specific medical diagnoses and procedures during admission; without proper documentation, scores may not accurately reflect patients' medical complexity. Our quality improvement study aimed to improve the accuracy of SOI and ROM capture within the electronic medical record (EMR) through implementation of documentation initiatives. METHODS: Documentation interventions were introduced on an inpatient gynecologic oncology service in January 2017 as follows: educational in-service for faculty and residents; introduction of problem-based assessment/plans in EMR progress notes; distribution of a documentation tip badge to residents and fellows; production of a high-yield documentation tip video. Admission/discharge SOI and ROM (scaled 1 to 4) and admission type/diagnosis were collected from gynecologic oncology inpatients pre-(2015) and post-(2017) intervention. 528 inpatient encounters from 349 unique patients were queried. A one-sided Wilcoxon rank sum test queried the hypothesis that SOI and ROM scores were higher post- compared to pre-intervention. RESULTS: Among 349 included patients, 254 (72.8%) were admitted in 2015 and 95 (27.2%) in 2017. Median admission and discharge SOIs each increased from 2 to 3 after intervention; P=0.002 and P=0.002, respectively. Median admission and discharge ROMs each remained at 2 but with improvement in the IQR following intervention; P=0.005 and P=0.02, respectively. Stratified by admission type, a significant increase was observed in scores for surgical, but not medical, admissions. CONCLUSION: A robust educational intervention to improve physician coding accuracy resulted in higher SOI and ROM scores for surgical admissions.